2011
DOI: 10.1007/s10190-011-0206-4
|View full text |Cite
|
Sign up to set email alerts
|

Épidémiologie, étiologie et évolution des hémorragies digestives hautes au centre hospitalier universitaire de Fès, Maroc

Abstract: Objectif : L'hémorragie digestive haute (HDH) est une urgence fréquente en hépatogastroentérologie. Le profil épidémiologique des HDH reste mal connu dans notre pays. Le but de notre travail est de décrire le profil épidémio-logique, étiologique et évolutif des HDH et d'analyser les différents facteurs liés à la mortalité. Matériels et méthodes : Il s'agit d'une étude initialement rétrospective [2001][2002][2003][2004] puis prospective [2005][2006][2007][2008], ayant inclus tous les patients adultes qui se son… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In terms of outcomes, 44 studies reported mortality, 810,18,2030,3237,39,4143,4749,5255,58,6366,6871,7375 27 rebleeding, 8,19,20,22,25,2931,34,35,38–40,43,45,46,50,51,5557,60,68,70,72,…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In terms of outcomes, 44 studies reported mortality, 810,18,2030,3237,39,4143,4749,5255,58,6366,6871,7375 27 rebleeding, 8,19,20,22,25,2931,34,35,38–40,43,45,46,50,51,5557,60,68,70,72,…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the identified studies were cohort studies, of which 22 were prospective, 8 , 10 , 18 37 32 were retrospective, 9 , 38 68 and two were ambidirectional analyses. 69 , 70 One RCT, 71 one case–control, 72 and three cross-sectional studies 58 , 73 75 were also included in the systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations